2017
DOI: 10.1038/s41598-017-06190-3
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced anomalous valence crossover in cubic YbCu5-based compounds

Abstract: A pressure-induced anomalous valence crossover without structural phase transition is observed in archetypal cubic YbCu5 based heavy Fermion systems. The Yb valence is found to decrease with increasing pressure, indicating a pressure-induced crossover from a localized 4f 13 state to the valence fluctuation regime, which is not expected for Yb systems with conventional c–f hybridization. This result further highlights the remarkable singularity of the valence behavior in compressed YbCu5-based compounds. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…From the perspective of compositions and crystal structures, we dedicated some systematic work to the study of the R 2 Pd 2 X (R = Ce, Yb; X = In, Sn) compounds with the tetragonal Mo 2 FeB 2 structure type. , The Mo 2 FeB 2 structure is the most representative (more than 200 compounds) of the systems with the general composition (AE/R) 2 T 2 X (AE = alkaline earth metals or R = lanthanide block, T = late transition metals, and X = Mg, Zn, Cd, Al, Ga, In, Sn, Pb). Due to the remarkable electronic flexibility of this group, many of the compounds crystallizing in the Mo 2 FeB 2 type exhibit outstanding physical properties. Notably, no representative of this structure type is known with divalent rare earth metals like Eu and only a few containing Yb , or the chemically similar alkaline earth metals. This is probably due to the bigger sizes of these metals, which stabilize other structure types.…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of compositions and crystal structures, we dedicated some systematic work to the study of the R 2 Pd 2 X (R = Ce, Yb; X = In, Sn) compounds with the tetragonal Mo 2 FeB 2 structure type. , The Mo 2 FeB 2 structure is the most representative (more than 200 compounds) of the systems with the general composition (AE/R) 2 T 2 X (AE = alkaline earth metals or R = lanthanide block, T = late transition metals, and X = Mg, Zn, Cd, Al, Ga, In, Sn, Pb). Due to the remarkable electronic flexibility of this group, many of the compounds crystallizing in the Mo 2 FeB 2 type exhibit outstanding physical properties. Notably, no representative of this structure type is known with divalent rare earth metals like Eu and only a few containing Yb , or the chemically similar alkaline earth metals. This is probably due to the bigger sizes of these metals, which stabilize other structure types.…”
Section: Introductionmentioning
confidence: 99%
“…Recently notable examples of unique properties have been found in the Yb-T-X systems (T = transition metals, X = p-type elements). For instance, in a systematic search for new ytterbium-palladium indides and stannides 5,6 , we have synthesized Yb 2 Pd 2 Sn, where two quantum critical points (QCPs) occur under pressure 7,8 and under Sn/In doping 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In some of these compounds, e.g. YbPt 2 Sn and YbCo 2 Zn 20 , it was shown that the low temperature magnetic entropy is strongly shifted to higher temperature by applying magnetic fields, offering the interesting perspective to use these materials as efficient metallic refrigerant for adiabatic magnetization cooling 8,14 .…”
Section: Introductionmentioning
confidence: 99%
“…The application of hydrostatic-or chemical pressure implies a reduction of the unit cell volume 4 . Moderate hydrostatic pressure has negligible effects on the Yb 3+ valence, as confirmed by x-ray absorption spectroscopy in the partial fluorescence yield mode (PFY-XAS) and by resonant x-ray emission spectroscopy (RXES) under applied pressure 7 . Also the In/Sn substitution, (chemical pressure), does not distinctly affect valence, since dc susceptibility measurements indicate almost constant Yb magnetic moments in the paramagnetic state, independent of tin concentration (App.…”
Section: Discussionmentioning
confidence: 87%
“…Thus, an increase in pressure "squeezes" one of the Yb 4 f -electrons out of its shell, driving the non magnetic Yb 2+ (4 f 14 , J = 0) to magnetic Yb 3+ (4 f 13 , J = 7/2, µ = 4.52 µ B ). As a consequence, the Kondo effect is weakened, while the RKKY-mediated exchange interactions among the Yb ions are enhanced, a favorable condition for the onset of a long-range magnetically ordered phase [3][4][5][6][7] . This is precisely the case of Yb 2 Pd 2 In 1−x Sn x , previously investigated via macroscopic techniques and lately studied also via µSR, at both ambient-and high-pressure conditions, in the stoichiometric x = 1 case 6 .…”
Section: Introductionmentioning
confidence: 99%